2008
DOI: 10.1021/la800793e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oscillation Induced Periodic Swelling and Shrinking of a Polymeric Multilayer Investigated with a Quartz Crystal Microbalance

Abstract: Poly(acrylic acid- co-3-azidopropyl acrylate) and poly(acrylic acid- co-propargyl acrylate) have been alternately fabricated into a multilayer via the click reaction. The layer-by-layer deposition was monitored with a quartz crystal microbalance with dissipation (QCM-D) in real time. The response of the multilayer under continuous flow of a bromate-sulfite-ferrocyanide solution with pH oscillation has also been investigated by use of QCM-D. As the pH oscillates between 3.1 and 6.6, either the frequency shift (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
(110 reference statements)
2
21
0
Order By: Relevance
“…The ratio between the areas of these two peaks is in agreement with an almost complete reaction between the azide and alkyne groups (see detailed discussion in the Supporting Information). In addition, the peaks centered at 401 and 405 eV characteristic of azides12 are absent from the XPS spectrum. These results provide strong evidence of a quasiquantitative reaction between the two functionalized PAA polyanions.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio between the areas of these two peaks is in agreement with an almost complete reaction between the azide and alkyne groups (see detailed discussion in the Supporting Information). In addition, the peaks centered at 401 and 405 eV characteristic of azides12 are absent from the XPS spectrum. These results provide strong evidence of a quasiquantitative reaction between the two functionalized PAA polyanions.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, Tang et al reported the oscillatory behavior of a pH-responsive LbL assembly, which was studied by means of QCM-D [ 66 ]. The multilayer was assembled by the assembly and “click” reaction of poly(acrylic acid- co -3-azidopropyl acrylate) (poly(AA- co -Az)) and poly(acrylic acid- co -propargyl acrylate) (poly(AA- co -PA)) directly on the QCM crystal resonator, which was previously functionalized with a primer layer of alkyne-modified branched poly(ethyleneimine) ( Figure 3 a).…”
Section: Chemo-mechanical Oscillations In Surface-grafted Single Pmentioning
confidence: 99%
“… ( a – c ) Chemical structure and schematic representation of the pH-oscillating layer-by-layer assembly, crosslinked with a click chemistry approach. ( d ) Corresponding frequency and dissipation shifts monitored by QCM-D. Reproduced with permission from [ 66 ], American Chemical Society, 2008. …”
Section: Figurementioning
confidence: 99%
“…The covalent bonds between PAA chains allow a reversible swelling of the film when the pH is changed after buildup. 192 The optimal buildup conditions for this azide-and alkyne-functional PAA-based system were investigated. 193 The obtained films are thicker when the pH of the solution is adjusted to 2.5, the grafting ratio of PAA is 30%, the adsorption time equal to 10 minutes and the ionic strength fixed to 150 mM.…”
Section: C1 Discovery and Mechanismmentioning
confidence: 99%